1985
DOI: 10.1148/radiology.157.2.3901112
|View full text |Cite
|
Sign up to set email alerts
|

Whole-breast US imaging: four-year follow-up.

Abstract: Between March 1980 and April 1981, 1,140 women underwent physical examination, xeromammography, and whole-breast ultrasound (US) using a whole-breast water path system. Results of each study were interpreted independently by separate observers in a blind fashion. Biopsy revealed 125 cancers in 127 breasts. Findings were considered to be suspicious for carcinoma in 199 women based on physical examination, in 201 based on mammograms, and in 255 based on US scans. Physical examinations were able to reveal 91% (11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
2
6

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(25 citation statements)
references
References 0 publications
2
15
2
6
Order By: Relevance
“…On the other hand, additional cancers detected by ultrasonography in women over age 50 were seven, compared with 112 detected at mammography, thus accounting for a relative sensitivity increase of 6.2%. Overall, the present experience confirms the possibility of ultrasonography detecting mammographically occult cancer in dense breasts [1,18] although we agree with Kopans [19][20][21][22] that this does not constitute sufficient evidence to support the introduction of this policy in current screening practice. However, the observed cancer detection rate at ultrasonography is promising as to final results of ongoing prospective studies.…”
Section: Discussioncontrasting
confidence: 61%
“…On the other hand, additional cancers detected by ultrasonography in women over age 50 were seven, compared with 112 detected at mammography, thus accounting for a relative sensitivity increase of 6.2%. Overall, the present experience confirms the possibility of ultrasonography detecting mammographically occult cancer in dense breasts [1,18] although we agree with Kopans [19][20][21][22] that this does not constitute sufficient evidence to support the introduction of this policy in current screening practice. However, the observed cancer detection rate at ultrasonography is promising as to final results of ongoing prospective studies.…”
Section: Discussioncontrasting
confidence: 61%
“…So, there is a great need for development of additional reliable methods to complement the existing diagnostic procedures to avoid unnecessary biopsy. The initial screening studies 7,8 with sonography in the 1980s were not as successful as the present study. A decade later favorable results for sonography of palpable breast masses were also noted in more studies.…”
Section: Ultrasonographic Discrimination Of Benign and Malignantcontrasting
confidence: 73%
“…Sickles et al 11 found that sonography missed 11 of 41 palpable malignancies, whereas mammography missed only 1. Kopans et al 12 had similar results: sonography did not visualize 34 of the 127 palpable cancers, whereas mammography missed only 8 of them. A decade later, however, Gordon et al 13 noted 58 mammographically occult cancers detected by sonography, of which 43 (74%) were palpable.…”
Section: Discussionmentioning
confidence: 82%